Síntese, caracterização e investigação das propriedades antitumorais in vitro em modelos 2D e 3D de compostos de coordenação de Pd(II) com tiossemicarbazidas e bis(difenilfosfina)alcanos - Fortaleza, Dario Batista (Universidade Federal de São Carlos, 2024)
The increasing incidence of cancer highlights the urgent need to develop new molecules with therapeutic potential. In this context, this study presents the synthesis and characterisation of six new Pt(II) complexes containing derivatives of thiosemicarbazides and bis(diphenylphosphines). The compounds were analysed using techniques such as 1H and 31P NMR spectroscopy, high resolution mass spectrometry, infrared spectroscopy, UV-vis spectroscopy, molar conductivity and single crystal X-ray diffraction where available. These approaches allowed the identification of a molecular structure with a flat square geometry around the metal ion, with the ligands coordinating in a bidentate manner. In addition, lipophilicity and stability in different solutions were evaluated, as well as interaction assays with biomolecules, including DNA, topoisomerase and HSA, to understand the mode of action of the compounds and their ability to be transported by the organism. The antitumour properties of all the compounds were evaluated in various tumour cell lines, including breast (MCF-7 and MDA-MB-231), ovarian (A2780 and A2780cis), lung (A549) and prostate (Du-145) cancers and non-tumour lung cells (MRC-5). Among the complexes tested, the PdB3 complex showed the best results against ovarian and breast tumour cells, with an IC50 value of approximately 1µM. In addition, PdB3 showed the ability to inhibit cell proliferation in a dose-dependent manner in colony formation assays. Cell morphology, cell cycle and flow cytometry assays indicated that the compounds induced cell death by apoptosis. These promising results were further validated in a more physiologically relevant context with assays performed in 3D cell cultures (spheroids). The results demonstrated the superior cytotoxic potential of PdB3 compared to cisplatin in the cisplatin-resistant A2780cis cell line. This highlights the potential of the structurally simple compounds synthesised in this study and suggests that this molecular scaffold could be an important strategy in the development of effective anti-tumour agents.
Synthesis, characterization and investigation of in vitro antitumor properties in 2D and 3D models of Pd(II) coordination compounds with thiosemicarbazides and bis(diphenylphosphine) alkanes.
Keywords: Pd (II); Tiossemicarbazidas; Bisfosfina; Antitumoral; Células 3D; CIENCIAS BIOLOGICAS::MICROBIOLOGIA; CIENCIAS EXATAS E DA TERRA::QUIMICA